2019
DOI: 10.1128/aac.01531-18
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in cdsA and pgsA Correlate with Daptomycin Resistance in Streptococcus mitis and S. oralis

Abstract: We investigated the ability of several recent clinical viridans group streptococci (VGS) bloodstream isolates (Streptococcus mitis/S. oralis subgroup) from daptomycin (DAP)-naive patients to develop DAP resistance in vitro. All strains rapidly developed high-level and stable DAP resistance. Substitutions in two enzymes involved in the cardiolipin biosynthesis pathway were identified, i.e., CdsA (phosphatidate cytidylyltransferase) and PgsA (CDP-diacylglycerol-glycerol-3-phosphate-3-phosphatidyltransferase). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 20 publications
7
44
1
Order By: Relevance
“…Although DAP has demonstrated excellent in vitro activity against S. mitis/oralis, several studies have reported that more than 25% of DAPsusceptible (DAP-S) strains rapidly develop high-level (MICs of Ͼ256 g/ml) and durable DAP resistance (DAP-R) during in vitro exposures to DAP; a similar observation has been made in vivo in experimental IE (2,12). The mechanism of DAP-R in S. mitis/oralis involves, at least in part, single nucleotide polymorphisms (SNPs) within cdsA (a locus encoding an enzyme responsible for catalyzing the first committed step in cardiolipin biosynthesis) and pgsA, encoding the enzyme responsible for the synthesis of phosphatidylglycerol (13)(14)(15). Such SNPs result in essentially no detectable cardiolipin production (14,15).…”
mentioning
confidence: 70%
“…Although DAP has demonstrated excellent in vitro activity against S. mitis/oralis, several studies have reported that more than 25% of DAPsusceptible (DAP-S) strains rapidly develop high-level (MICs of Ͼ256 g/ml) and durable DAP resistance (DAP-R) during in vitro exposures to DAP; a similar observation has been made in vivo in experimental IE (2,12). The mechanism of DAP-R in S. mitis/oralis involves, at least in part, single nucleotide polymorphisms (SNPs) within cdsA (a locus encoding an enzyme responsible for catalyzing the first committed step in cardiolipin biosynthesis) and pgsA, encoding the enzyme responsible for the synthesis of phosphatidylglycerol (13)(14)(15). Such SNPs result in essentially no detectable cardiolipin production (14,15).…”
mentioning
confidence: 70%
“…mitis/S. oralis strains (57). We conclude that the sole candidate for CPT activity in SM43, PgsA, does not catalyze PC biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…These motifs may affect the overall resistance of beta‐lactam antibacterials in this clinical isolate. Moreover, It is known that G221V, R230H, and D249E of cdsA gene and G52S of pgsA gene are involved in DAP resistance . However, these substitutions could not be confirmed from this clinical strain.…”
Section: Case Reportmentioning
confidence: 77%
“…In our patient, substitutions in the amino acid motif of the PBP2b and the PBP2X enzyme might have partially contribute the resistance of this microorganism to beta‐lactam antibiotics. Recently, it was reported that loss‐of‐function mutations in cdsA (encoding a phosphatidate cytidylyltransferase) contributed the resistance to DAP and mutations in cdsA , and pgsA (encoding a phosphatidyl glycerophosphate synthetase) correlated with DPT resistance in 2 S oralis strains (32 364 derivatives: D1 and D5) were reported . There was not substitution of G221V, R230H, and D249E of cdsA gene and G52S of pgsA gene, suggested that other resistance mechanisms might be involved.…”
Section: Discussionmentioning
confidence: 99%